1995
DOI: 10.1038/376602a0
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of bZIP proteins by the human T-cell leukaemia virus transactivator Tax

Abstract: Human T-cell leukaemia virus type I (HTLV-I) Tax protein increases the DNA binding of many cellular transcription factors that contain a basic region-leucine zipper (bZIP) DNA-binding domain. bZIP domains comprise a leucine-rich dimerization motif and a basic region that mediates DNA contact. How Tax recognizes diverse bZIPs is not understood. Here we show that no specific sequence of the leucine zipper is required for a Tax response. In contrast, the basic region is essential for the Tax-mediated DNA-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
135
3

Year Published

1995
1995
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 16 publications
8
135
3
Order By: Relevance
“…Although all ATF proteins bind to the same DNA site, it has been speculated that di erent ATF proteins selectively bind to ATF sites within di erent promoters. Several members of the ATF-1/CREB family have been shown to bind to the Tax responsive elements (TRE) in the presence of Tax through their basic and leucine-zipper (bZIP) domains (Wagner and Green, 1993;Perini et al, 1995). Tax has been shown to promote dimerization and increase the DNA binding activity of several bZIP proteins (Wagner and Green, 1993;Perini et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all ATF proteins bind to the same DNA site, it has been speculated that di erent ATF proteins selectively bind to ATF sites within di erent promoters. Several members of the ATF-1/CREB family have been shown to bind to the Tax responsive elements (TRE) in the presence of Tax through their basic and leucine-zipper (bZIP) domains (Wagner and Green, 1993;Perini et al, 1995). Tax has been shown to promote dimerization and increase the DNA binding activity of several bZIP proteins (Wagner and Green, 1993;Perini et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several members of the ATF-1/CREB family have been shown to bind to the Tax responsive elements (TRE) in the presence of Tax through their basic and leucine-zipper (bZIP) domains (Wagner and Green, 1993;Perini et al, 1995). Tax has been shown to promote dimerization and increase the DNA binding activity of several bZIP proteins (Wagner and Green, 1993;Perini et al, 1995). Additionally, ATF-3 has also been shown to interact with Tax (Low et al, 1994) at the cAMP responsive element of the human proenkephalin gene.…”
Section: Discussionmentioning
confidence: 99%
“…The Bombyx mori MBF1 binds to a DNA binding region of FTZ-F1, called FTZ-F1 box, and its yeast counterpart binds to the DNA binding basic region of the bZIP domain of GCN4 (Ueda et al 1992;Li et al 1994;Takemaru et al 1997;Takemaru et al 1998). The binding of MBF1 to FTZ-F1 or GCN4 stimulates their bindings to the target DNA sequences in a similar manner as the human T-cell leukaemia virus transactivator Tax does (Baranger et al 1995;Perini et al 1995). In this study, we identified the well-structured core domain of MBF1 which is capable of binding to TBP, and determined its secondary structure by NMR.…”
Section: Introductionmentioning
confidence: 99%
“…Of the four complexes (I, II, II1 and IV) detected in the EMSA of peripheral blood T cell nuclear proteins with preimmune rabbit serum (P), incubation with R1090 CREB antiserum (I) supershifted complexes I and II to the complexes denoted as Is and IIs and eliminated complex III. (B) Cross-competition of binding for EMSA complexes I, II, III and IV in T cell nuclear extracts (TNE) with the IH21CRE 32P-radioactively labeled probe 1H21CRE (lanes [13][14][15][16][17] indicate that competition with a 100-fold excess of unlabeled probe I H21CREwt competes all four complexes while the mutated probes 1H21CRE-mut, 1H21CREGmut and 1H21CRETTmut compete only complexes Ill and IV. Bacterially expressed recombinant CREM binds effectively to the -~2P-labeled oligonucleotides corresponding to the three 21-bp repeats of HTLV-I LTR (lanes 18 20).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, Tax is believed to indirectly interact with CREs of the HTLV-I 21-bp repeats by forming protein-protein complexes with transcription factors [12,13]. It has been reported that Tax stabilizes the binding of CREB and other CRE-binding proteins to the CREs specifically in the 21-bp repeats of the HTLV-I promoter by interactions with the basic region/leucine zipper domain involved in DNA-binding [14][15][16]. Here we report evidence that Tax stimulates CREB-mediated transcription of the HTLV-1 LTR by a mechanism in addition to the stabilization of DNA-binding.…”
Section: Introductionmentioning
confidence: 99%